DOMAINS OF RAILWAY TRAFFIC IN THE CZECH REPUBLIC, WHICH NEED THE SAFETY IMPROVEMENT - Dana Procházková; Jan Procházka; Tomáš Kertis (Acta Polytechnica CTU Proceedings)
The paper analyses the railway accidents sources in the Czech Republic on the basis of knowledge on complex system behaviour. It derives seven categories of sources of railway accidents. The individual categories include the accident sources from the same field domain. These domains are: technical related to rail traffic vehicles; technical related to rail infrastructure and railway station; railway operation control – organizational causes; railway operation control – cyber causes; control of rail traffic vehicles; attack on the train; domain legislative and other. The results show that for railway traffic safety improvement, it is necessary to pay attention to all categories, and especially to these that lead to organizational accidents origination.